2015
DOI: 10.1021/acs.jchemed.5b00184
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Higher-Order Thinking in General Chemistry by Scaffolding Student Learning Using Marzano’s Taxonomy

Abstract: An emphasis on higher-order thinking within the curriculum has been a subject of interest in the chemical and STEM literature due to its ability to promote meaningful, transferable learning in students. The systematic use of learning taxonomies could be a practical way to scaffold student learning in order to achieve this goal. This work proposes the use of Marzano's Taxonomy of Learning. Because it offers a functional way to distinguish lower from higher-order thinking, the taxonomy is particularly useful to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 17 publications
1
44
0
3
Order By: Relevance
“…Nelson (2012) found that students recognized the academic value of technology as it helped them to access a wide range of resources, and take control of their learning. Toledo and Dubas (2016) proposed the use of Marzano's taxonomy of learning, because it offers a functional way to distinguish lower to higher-order thinking, and is particularly useful to instructors interested in helping students develop higher-order thinking skills in science. Godor (2016) argued that student learning approaches research has been built upon the notions of deep and surface learning.…”
Section: The Problem-based Learning and Academic Achievementsmentioning
confidence: 99%
“…Nelson (2012) found that students recognized the academic value of technology as it helped them to access a wide range of resources, and take control of their learning. Toledo and Dubas (2016) proposed the use of Marzano's taxonomy of learning, because it offers a functional way to distinguish lower to higher-order thinking, and is particularly useful to instructors interested in helping students develop higher-order thinking skills in science. Godor (2016) argued that student learning approaches research has been built upon the notions of deep and surface learning.…”
Section: The Problem-based Learning and Academic Achievementsmentioning
confidence: 99%
“…The results show that instructor-generated prompts from an expert or teacher made the students solve the chemistry problems significantly better than students who developed their own peer-prompts or students who at first developed their own prompts and thereafter revised them with help from the instructor. In a US study on general chemistry at university level, a hierarchical taxonomy was used to design a course aiming to scaffold students' learning through encouraging higher-order thinking (Toledo & Dubas, 2016). Early observations from that study indicate that students evaluated the different instruments implemented in their courses (scaffolding instruction, scaffolding assessment, and feedback) quite positively, claiming that all course materials had a positive impact on their learning.…”
Section: Conceptual Learning and Problem-solvingmentioning
confidence: 99%
“…There are four distributions of students' hierarchical cognitive levels --retrieval, comprehension, analysis, and knowledge utilization in Marzano's spectrum (Marzano & Kendall, 2007) with brain-based learning. Toledo and Dubas (2016) unanimously noticed that Marzano's taxonomy could describe students' cognitive levels of lower-order and higher-order thinking abilities clearly with the framework of spectrum. Students' lower-order thinking abilities included both retrieval and compression tasks during which students were required to obtain the rule-based learning, the accurate reasoning information and integrated comprehensive understanding.…”
Section: Cognitive Levels Of Marzano's Taxonomymentioning
confidence: 99%
“…The basic framework of the HOCS-centered diagnostic evaluation instrument (HODEI) follows four hierarchical levels in Marzano's taxonomy spectrum. Four hierarchical cognitive levels are included as retrieval, comprehension, analysis, and knowledge utilization shown in Figure 1 (Toledo & Dubas, 2016). The detailed discussions of four hierarchical cognitive levels, consist of level 1 (L1) as a retrieval task, level 2 (L2) as a comprehension task, level 3 (L3) as an analysis task and level 4 (L4) as a knowledge utilization task.…”
Section: General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation